2000
DOI: 10.1007/s004230050002
|View full text |Cite
|
Sign up to set email alerts
|

Inflammatory response after laparoscopic and conventional colorectal resections - results of a prospective randomized trial

Abstract: IL-6 and CRP plasma levels were lower after laparoscopic than conventional colorectal resections. The less intense inflammatory response may be an indicator of the milder surgical trauma inflicted by laparoscopic than conventional colorectal resection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
125
2
6

Year Published

2002
2002
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 190 publications
(140 citation statements)
references
References 38 publications
(44 reference statements)
7
125
2
6
Order By: Relevance
“…Prospective randomized and non-randomized trials have compared the postoperative changes in immunologic and inflammatory parameters of different surgical procedures [6, 8, 9, 10, 11, 12, 13, 14, 15, 16, 17, 18, 19, 20, 21, 22, 23, 24, 25, 26, 27, 28, 29, 30, 31, 32, 33, 34, 35, 36, 37, 38, 39, 40, 41, 42, 43, 44, 45, 46](table 1, 2). Most studies were performed in patients undergoing cholecystectomy, mainly showing a less pronounced postoperative increase in C-reactive protein, IL-1 and IL-6 for the laparoscopic approach, while the results of the systemic cellular changes differed between the different studies [9, 10, 13, 18, 22, 25, 27, 30, 32, 34, 39, 44].…”
Section: Clinical Trials Comparing the Impact Of Laparoscopic And Conmentioning
confidence: 99%
“…Prospective randomized and non-randomized trials have compared the postoperative changes in immunologic and inflammatory parameters of different surgical procedures [6, 8, 9, 10, 11, 12, 13, 14, 15, 16, 17, 18, 19, 20, 21, 22, 23, 24, 25, 26, 27, 28, 29, 30, 31, 32, 33, 34, 35, 36, 37, 38, 39, 40, 41, 42, 43, 44, 45, 46](table 1, 2). Most studies were performed in patients undergoing cholecystectomy, mainly showing a less pronounced postoperative increase in C-reactive protein, IL-1 and IL-6 for the laparoscopic approach, while the results of the systemic cellular changes differed between the different studies [9, 10, 13, 18, 22, 25, 27, 30, 32, 34, 39, 44].…”
Section: Clinical Trials Comparing the Impact Of Laparoscopic And Conmentioning
confidence: 99%
“…2). Schwenk et al [36] also observed significantly lower IL-6 and CRP plasma levels after laparoscopic than after conventional colorectal resections while IL-1RA and IL-10 levels showed no significant differences between both study groups. Moreover, the evaluation of the immune status after laparoscopic and conventional colorectal surgery by flow cytometry revealed significantly higher numbers of circulating natural killer cells in patients after minimal invasive colorectal resection ( fig.…”
Section: Immunological Effectsmentioning
confidence: 88%
“…In addition, LAPR avoids laparotomy which is painful. As result, recovery time is shorter which shortens the postoperative hospital stay [9] After finishing treatment, these patients were followed by CEA every 3 months, repeat colonoscopy one year after diagnosis, CT chest and abdomen annually and physical exam and history every 3 months. Present studies [1] [4]…”
Section: Discussionmentioning
confidence: 99%